Análise numérica e experimental de um snap-fit utilizado em componentes de um refrigerador - Haring, Gabriel Mora (Universidade Federal de São Carlos, 2022)
The home appliances sector is disputed by large companies, which, in order to remain competitive, are in a continuous search for improvements and cost reductions. The great engineering challenge is to reduce costs while maintaining the functionality, robustness and quality of the product, otherwise, valuable company resources can be wasted and generate catastrophic results once the product reaches the final consumer. In this way, studies are needed to prove the effectiveness of the modifications, thus increasing the level of confidence for project implementation. This document performs a numerical and experimental analysis of the snap-fit between polymeric clips and a metallic complement, aiming to guarantee the functionality and quantify the complement extraction force peak. The snap-fit disengagement simulation with theoretical and real geometry was performed using the finite element method, using the ANSYS software, the following step, experimental extraction test, was carried out in the laboratory, using a Cartesian robot. The results showed that the snap-fit function is adequate and the peak numerical and experimental extraction forces are significantly above the specification of the internal standard, enabling cost reduction proposals.
Numerical and experimental analysis of a snap-fit used in refrigerator components
Keywords: Snap-fit; Simulação funcional; Força de extração; Elementos finitos; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; 9. Indústria, Inovação e Infraestrutura